Potential Risk Analysis of Tailings Dam under Preloading Condition and Its Countermeasures - Wang, Shuren; Zhang, Haiqing; Zou, Zhengsheng; Wang, Ping; Yu, Tao (Journal of Engineering and Technological Sciences, 2015)
It is very important for mine production safety to ensure the stability of the tailings dam. Taking a flatland tailings pond as the background, a threedimensional  computational model was built based on a  tailings dam under mullock heap  preloading condition. Considering  the current operating  water level conditions, a liquid-solid coupling analysis of the model was conducted.The deformation characteristics of the tailings dam were revealed during successive preloading at the front of the dam. The safety factor and the potential slide face of the tailings dam were calculated under different conditions using the strength reduction method. The results show that the tailings dam in its current condition is basically stable, but if the mullock heap continues to be heightened, the tailings dam will become unstable. Therefore, in order to limit the height of the mullock heap, establishing a monitor and early warning mechanism are put forward to ensure mine production safety.